ANALISIS EFISIENSI ALOKATIF FAKTOR-FAKTOR PRODUKSI USAHATANI JAGUNG HIBRIDA DI KAWASAN USAHA AGRIBISNIS TERPADU (KUAT) RASAU JAYA KOMPLEK KABUPATEN KUBU RAYA - SUSILAWATI, SUSILAWATI; YUDIONO, SUGENG; SUYATNO, ADI (Jurnal Social Economic of Agriculture, 2015)
This study, entitled the Analysis of Efficiency of Designated Area on Producing Factors on Hybrid Corn at Joined Agribisnis Area (Kawasan Usaha Agribisnis Terpadu), Rasau Jaya Complex in Kuburaya Regency, aims to investigate the efficiency of using producing factors applied by famers in Bintang Mas village on Hybrid Corns. This research is also to analyse the level of scale of corn farmimg in Bintang Mas village. The methodology of this research is survey with Bintang Mas village as the place for the research held in Rasau Jaya Distrct, Kubu Raya Regency.         Kubu Raya is one of the places which plants corns and has become one of the centers for corn farming. It is also a designated area on corn farming. There are about 105 familiies working in this farming. The tool of the researach is simple random sampling. The scores for Adjusted R Square on this hybrid corn regression is 0,781 (78%). The research finding shows that the use of hybrid corn seeds, urea fertiliser, nitrofosca fertiliser, herbiside, and work have been working efficiently. Natural fertiliser has been used efficiently for 2.732 kg/ha. According to return to scale, the corn farming in Bintang Mas village is 2,21. This shows that the farming has an increase trend (increasing return to scale)